Integrasi Budaya Lokal Baduy dalam Pembelajaran Bahasa dan Sastra Indonesia di Sekolah Dasar dalam Perspektif Multikultural - Hatima, Yoma (Universitas Nusa Cendana, 2025)
Learning Indonesian Language and Literature in elementary schools has a strategic role in instilling national values, local wisdom, and multiculturalism to students. This literature study aims to analyze the integration of local culture of the Baduy community in learning Indonesian Language and Literature in elementary schools from a multicultural education perspective. Baduy culture, which is full of traditional values, simplicity, and harmony with nature, is a rich and authentic source of learning to shape character and broaden students' insight into diversity. This study uses a literature study method by reviewing various sources such as scientific journals, reference books, and research reports related to the topic of local cultural integration, learning Indonesian Language and Literature, and multicultural education. The results of the analysis show that folklore, traditional pantun, and traditional Baduy expressions can be used as teaching materials that not only enrich language competence but also instill local wisdom values. In addition, thematic and contextual approaches have proven effective in aligning local cultural materials with the Indonesian Language curriculum. This study recommends the importance of teacher training, development of locally-based teaching media, and educational policies that support cultural integration in the curriculum. Thus, learning Indonesian Language and Literature in Elementary School can be a strategic vehicle in forming an inclusive national identity rooted in local wisdom.